A novel model reduction approach for blisks with blend repairs and small mistuning. (15th July 2023) - Zhou, Biao; Berruti, Teresa Maria
Abstract: Blisks undergoing blade repairs by the 'blending' technique, require structural analyses to assess possible dynamic issues and also to define the blend repair limits, etc. This usually leads to prohibitive computational costs due to the large-scale full-order industrial blisk finite element models. This paper presents a novel model reduction approach, termed 'Sector Mode Assembling Reduction Technique' (SMART), for blisks with small intrinsic stiffness/geometric mistuning under blend repairs. The SMART approach starts from substructuring the full-order blisk finite element model into two kinds of components: the blended sectors with incompatible meshes and the pristine sectors with small mistuning. The truncated cyclic modes, independently computed by sector-level expansions for the two kinds of components, are strategically assembled into the SMART reduction mode basis in a sector-level form. This is beneficial for generating the reduced-order models since all the projection processes are maintained in the sector-level computations with a relatively low computational cost and memory requirement. Numerical cases demonstrate that the reduced-order models derived by the SMART approach produce structural dynamics in very good accordance with the corresponding full-order blisk finite element models, meanwhile offering the advantage of high computational efficiency and the flexibility to upgrade the reduced-order model with newly repaired blades. Highlights: The SMART approach is proposed for blisks with small intrinsic mistuning under blend repairs. The full blisk model is substructured the blended sectors and the pristine sectors with small intrinsic mistuning. The truncated cyclic modes for the two components are assembled into the reduction mode basis. The SMART approach allows the flexibility to upgrade the reduced-order model with newly repaired blades.